2022
DOI: 10.1111/jdv.18142
|View full text |Cite
|
Sign up to set email alerts
|

Punctate Administration of Ficin as a human and animal model of non‐histaminergic itch

Abstract: Background Ficin, a cysteine protease derived from fig‐tree latex, has been reported to elicit itch and nociceptive sensations, though quantitative sensory studies are lacking. Cowhage containing the pruritic cysteine Mucunain, on the contrary, has been widely studied as activating polymodal nociceptors and eliciting a histamine‐independent itch. Objectives We tested whether ficin in heat‐inactivated cowhage spicules would elicit itch and nociceptive sensations in humans, and analogous behaviours in mice, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Actually, out of 341, three patients (0.88%) claimed allergy reaction to fig, two of them reporting OAS to the fruit ingestion and the third one reported an itchy reaction following skin contact to pruning but none of them was IgE positive to Fic c Ficin. Indeed, the literature reports describe that cysteine proteases can evoke itch in the absence of any allergic reaction [71,72]. Therefore, at least in the investigated population of allergics, and on the basis of the in vitro tests here reported, the fig cysteine protease does not appear to be the culprit of the reported allergy reactions due to fig exposure.…”
Section: Discussionmentioning
confidence: 64%
“…Actually, out of 341, three patients (0.88%) claimed allergy reaction to fig, two of them reporting OAS to the fruit ingestion and the third one reported an itchy reaction following skin contact to pruning but none of them was IgE positive to Fic c Ficin. Indeed, the literature reports describe that cysteine proteases can evoke itch in the absence of any allergic reaction [71,72]. Therefore, at least in the investigated population of allergics, and on the basis of the in vitro tests here reported, the fig cysteine protease does not appear to be the culprit of the reported allergy reactions due to fig exposure.…”
Section: Discussionmentioning
confidence: 64%
“…30 Chronic exposure to the exogenous cysteine protease Ficin contained in fig plants may promote sensitization to fig aeroallergens. 31 Prolonged contact of the pre-sensitized AD skin with cysteine proteases can lead to the release of alarmins and in consequence may promote Th2-type response and sensitization. 32,33 The sensitization of cowhage-activated mechanosensitive polymodal C-fibres in non-lesional skin of AD might also explain wool intolerance phenomenon, 34,35 which is one of the minor criteria of AD.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, ficin possesses antioxidant and whitening effects in skin cells and has the potential to be developed as a novel bio-cosmetic substance (Cho et al, 2019). According to a recent study conducted by Malewicz et al, (2022), it has been found that ficin may be effective in translating mechanistic studies on the brain processes of cysteine proteases' pruritic and nociceptive actions. Furthermore, another study by Baidamshina et al, (2020) has demonstrated the stability and beneficial effects of chitosan-immobilized Ficin, which suggests that its addition to materials used in wound dressing may enhance the effectiveness of antimicrobial treatment and promote wound healing by preventing biofouling…”
Section: Discussionmentioning
confidence: 99%